Adverse Drug Reactions and Outcome Analysis of MDR Tb Patients on Dots Plus Regimen - Vishakha K Kapadia; Sanjay B Tripathi (Medsci Publications, 2016)
Introduction: The emergence of drug resistant mycobacteria has become a significant public health problem world over creating an obstacle to effective TB control. Present study was conducted to evaluate pattern and frequency of adverse drug reactions (ADR) of CAT IV, to analyze demographic, radiological and bacteriological profile and treatment outcome in MDR TB patients. Method: Total 102 MDR TB patients (with in vitro resistance to Isoniazid and Rifampicin) were analyzed retrospectively who had completed treatment from august 2007 to June 2014. Analysis was made for extent of lung lesion, correlation of sputum smear and culture conversion with clinical and radiological improvement, risk factors for adverse outcome and adverse drug reactions. Result: Forty six patients (45.09%) were cured/treatment completed, nine patients (8.82%) failed, 21 patients (20.05%) defaulted and 26 patients (25.49%) died of total 102 patients. Mean time for sputum smear and culture conversion were 4.2±2.0 and 4.19±2.3 months, respectively. Advanced lung lesion, cavitations, poor adherence to treatment and BMI less than 18 are variables associated with poor outcome. Fifty (52.94%) patients experienced adverse drug reactions and 42 of them required drug modifications. Conclusion: The ADRs were more common in the first 60 days of the regimen & in patient with BMI<18. Hence vigilant monitoring is required for these types of patients during the initial period. Sputum smear and culture conversion are very well correlated with clinical and radiological improvement.